Construction of Evaluation Indicator System for Rural Vitalization and Regional Variance Analysis - Wang, Yu; Jia, Yuankai; Li, Zhemin; Wang, Shengwei; Yu, Wen; Zhang, Xiaoyun; Han, Zhou (Transactions on Social Science, Education and Humanities Research, 2024)
Since the implementation of the rural vitalization strategy, how to set scientific and reasonable evaluation indicators to evaluate the results of rural vitalization has been of great theoretical and practical significance. This article, at the national, provincial and regional level respectively, applies entropy to create the method for determining the weight of parallel indicators, establish basic indicators and sub-indicators, and determine the weight of different combinations of evaluation indicators through official data and survey data. According to research findings, rural vitalization of the whole country and different provinces have all developed between 2018 and 2022 compared to 2017, but to significantly varying degrees. The average score of rural vitalization nationwide shows a slight increase. In the meantime, Beijing, Shanghai, Zhejiang and Shandong rank near the top in terms of their level of rural vitalization, while Chongqing, Xinjiang, Gansu, Guizhou, Qinghai and Xizang rank low. The average level of rural vitalization at the regional level has all improved, but to evidently different degrees. Among them, the average scores of rural vitalization of southeast coastal area and Huang-Huai-Hai area both exceed 0.055, reaching a high level, immediately followed by the northeast China and the middle reaches of the Yangtze River. Rural vitalization in the Loess Plateau region and the arid areas in northwest China is at merely a mid-to-low level nationwide, despite its great improvement in recent 5 years, particularly in the Loess Plateau region. The arid areas in northwest China and the Qinghai-Xizang Plateau region have also made marked progress in recent 5 years, especially the Qinghai-Xizang Plateau region, but still see much room for development. This article suggests making full use of government, society, enterprises and all other forces to balance resources and reduce regional differences by means of policy support, market and entrepreneur cultivation and experience sharing and so on, thus to improve the overall level of the country.